KAJIAN TEKNIS KEMAJUAN LUBANG BUKAAN YANG OPTIMAL PADA PENAMBANGAN BIJIH EMAS DI PT. DEMPO MAJU CEMERLANG KENAGARIAN TAMBANG KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN PROVINSI SUMATERA BARAT - RIRIN HANRIESTA BR MATONDANG; Raimon Kopa; Admizal Nazki (Journals Mining Engineering : Bina Tambang, 2021)
Absract. PT. Dempo Maju Cemerlang is a company focused in the gold mining industry in Indonesia. PT. Dempo Maju Cemerlang uses an underground mining system using the shrinkage method. Underground mining activities at PT. DMC is divided into two activities, namely production and development. Blasting activities play an important role in the mining cycle to unload ore or waste so that it can be taken out of the mining area. This study aims to produce openings as planned by the company with a better progress value. The success of a blasting can be judged by the results obtained. Blasting results at PT. DMC has not yet reached the progress target set by the company, namely 1.5 m / blasting. The average progress of each detonation is 1,216 m, the average actual blasting size is 20 cm, the actual blasting volume averages 4.0699 kg / m3 with an average powder factor value of 1.889 kg / ton, and the amount of explosives which is used for 22 blast holes, namely 20 kg. After designing and testing the recommended blasting geometry, the average progression value is 1.51 m, the resulting fragmentation is also better with an average size of 50 cm, an average volume of 5.0637kg / m3, an average PF value of 1.137 kg / ton, and the amount of explosives used for 22 blast holes is 15 kg. So after testing with the design geometry, an increase in the progress of the blasting hole was obtained by 0.294 m for one blasting, the volume also increased by approximately 0.9938 kg / m3, the PF value of the blasting result was smaller which meant that the fragmentation of the blasting result was more. good and there was a savings in the use of 5 kg of explosives for one front blasting.Keywords: Mine Progress, Blasting, Underground Mining, Blasting Results.